Reading/Writing Women in Myriam Warner-Vieyra's Juletane - Bella Brodzki (Studies in 20th & 21st Century Literature, 1993)
Voicelessness, alienation, confinement, deracination, rupture, exclusion, madness and exile: the thematic preoccupations of Myriam Warner-Vieyra's Juletane are familiar to readers of francophone Caribbean women's writing. The legacy of slavery and 20th century departmentalization have produced a complex politics of identity, whose points of reference and sites of longing—though privileged in a variety of ways in the psyches of Caribbean subjects—are Africa and France. The orphaned protagonist Juletane seeks love in Africa in the heady days before Independence. Warner-Vieyra uses the device of the fictional first-person journal mode to examine Juletane's disillusionment as well as the interplay of colonially-produced cultural differences among Caribbean and West African women in a traditional West African community. One of the effects of this devastating narrative is that Western feminist criticism's universalizing theories about reading and writing appear hopelessly reductive from a contemporary francophone African perspective.
Keywords: voice; voicelessness; alienation; confinement; deracination; rupture; exclusion; madness; exile; Myriam Warner-Vieyra; Juletane; francophone Caribbean women& #x27; s writing; slavery; Caribbean women; West African women; West African community Western feminist